1986
DOI: 10.1093/nar/14.5.2015
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence recognition by under-methylated analogues of triostin A

Abstract: Two new analogues of TANDEM (des-N-tetramethyl triostin A) have been synthesised in an effort to elucidate the molecular basis of DNA nucleotide sequence recognition in this series of compounds. Their binding preferences have been investigated by DNAase I footprinting and differential inhibition of restriction nuclease attack. The presence of a single N-methyl group on only one valine residue (in [N-MeVal4] TANDEM) abolishes the ability to recognise DNA, presumably because this antibiotic analogue has suffered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 25 publications
4
30
0
Order By: Relevance
“…We have shown that the best tetranucleotide binding site for TANDEM contains the sequence ATAT, consistent with the previous observation that it binds best to TpA steps which are flanked by A and T residues (8,9,17). However, the binding is strongly influenced by the identity of the surrounding bases and all TpA steps do not constitute good binding sites.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We have shown that the best tetranucleotide binding site for TANDEM contains the sequence ATAT, consistent with the previous observation that it binds best to TpA steps which are flanked by A and T residues (8,9,17). However, the binding is strongly influenced by the identity of the surrounding bases and all TpA steps do not constitute good binding sites.…”
Section: Discussionsupporting
confidence: 91%
“…Subsequent footprinting studies showed that TANDEM and its derivative [N-MeCys 3 ,N-MeCys 7 ]TANDEM bind to the dinucleotide TpA (8 -11), and this has been confirmed by NMR studies which have suggested mechanisms by which the ligand targets this sequence (12)(13)(14)(15)(16). However, several studies have suggested that TpA alone does not constitute the best binding sequence, and that the preferred sites are flanked by other AT residues (8,9,17,18), consistent with the observation that the ligand binds cooperatively to poly(dA-dT) (7). We have therefore analyzed the binding of this ligand to TpA when flanked by different base pairs, by quantitative DNase I footprinting using a novel DNA substrate which contains all possible 136 tetranucleotide sequences.…”
supporting
confidence: 58%
“…Footprinting studies eventually revealed that triostin A binds specifically to sequences centred around a CpG step, whereas TANDEM selectively recognizes TpA sites [14][15][16][17]. Most binding studies have been performed with [N-MeCys$, NMeCys(]TANDEM rather than with TANDEM itself, but the two synthetic drugs appear equivalent in terms of binding strength and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…However, it must be emphasized that the binding mode of these new lexitropsins is far from fully understood and that it is not yet possible to design reagents specifically targeted to desired sequences by this approach. Another direction of research involves the design of ligands with mixed binding modes, such as intercalator-peptide conjugates like TANDEM (Low et al 1986), and intercalatorminor-groove binder conjugates (Bailly et al, 1990). However, to date our knowledge of the sequencedependent variation in DNA structure and of the perturbation induced by simultaneous intercalation and groove binding is incomplete and does not allow a full * Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%